Synthesis, Characterization, Anticancer and In Silico ADME Properties of Caproic Acid Derivatives against P388 Cancer Cell Lines - Galuh Widiyarti; Andini Sundowo; Megawati Megawati; Teni Ernawati (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
The in-silico properties of absorption, distribution, metabolism, and excretion (ADME) and drugs likeness of caproic acid ester derivativeswere evaluated. The esterification of caproic acid from palm kernel oil with sitronelol and geraniol from citronella oil has been carried out using base (NaOH) catalyst. The cytotoxicity of ester compounds were also tested against P388 murine leukemia cancer cell lines using MTT method. Analysis of the ester productswere carried outusing spectroscopic (IR, MS and 1H-NMR) methods, which were confirmed that the desired compounds were successfully synthesized. Caproic acid ester derivatives showed higher anticancer activity compared to the parent caproic acid for P388 cancer cell lines. Citronellyl caproate with IC50 4.15x10-2µM has the strongeractivity than geranyl caproate with IC50 11x10-2 µM. ADME studies for the synthesized compounds revealed that the ester compounds have fulfill the Lipinski rule of five and has no carcinogenicity effect to rat or mouse.Key words: caproic acid, ester, P388, MTT, ADME